Peran Perceived Organizational Support dan Psychological Empowerment terhadap Kinerja Karyawan melalui Organizational Citizenship Behavior - Alfiana, Dhera (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
This research mainly explores the relationship between perceived organizational support and psychological empowerment to employee performance and organizational citizenship behavior as mediation variabel. causality research using census is type this reseacrh total of 50 employees of PT. Angkasa Pura I Juanda Surabaya participants in this study. The statistical analysis used PLS with help of smartpls 3.0 software. The result of this study explain that the perceived organizational support and psychological empowerment has a significant effect and positively to organizational citizenship behavior, perceived organizational and psychological empowerment has insignificant effect and positively to employee performance, organizational citizenship behavior has significant effect and positively to employee performance, organizational citizenship behavior as mediation has insignificant effect and positively between perceived organizational citizenshp behavior and psychological empowerment to employee performance.